Análise da composição dos gastos com alimentação no Município de São Paulo (Brasil) na década de 1990 Analysis of household expenditures with food in the city of S. Paulo in the 1990's - Sérgio Augusto Jábali Barretto; Denise Cavallini Cyrillo (Universidade de São Paulo, 2001)
OBJETIVO: Identificar as estruturas de consumo alimentar no Município de São Paulo, de 1990 a 1996, e compará-las com as derivadas de cestas de alimentos balanceados (CA). MÉTODOS: Por meio de pesquisas de orçamentos familiares, foram verificados os percentuais dos gastos domiciliares com três grupos de alimentos: semi-elaborados, industrializados e in natura (este foi enfocado com particular ênfase). Um índice de preços ao consumidor permitiu avaliar as variações nos custos relativos dos produtos. As CA foram elaboradas pela Programação Linear. RESULTADOS: De 1990 a 1996, aumentou a proporção dos gastos domiciliares com alimentos industrializados; tendência inversa foi constatada para os semi-elaborados; a percentagem referente aos in natura apresentou importante redução (35%). Essas mudanças não são explicadas satisfatoriamente pela variação nos preços relativos. As estruturas de consumo familiar mostraram-se diferentes das que são propostas pelas CA, e estas apresentaram, em geral, custos inferiores aos gastos domésticos com alimentos. CONCLUSÕES: Infere-se a existência de uma provável inadequação dietética nos domicílios de São Paulo e de riscos associados a uma ingestão insuficiente de legumes, verduras e frutas. OBJECTIVE: To identify food consumption patterns in the city of S. Paulo, from 1990 to 1996, and compare these patterns with those derived from nutritionally balanced food baskets (FB). METHODS: Household budget surveys were verified and the percentage of food expenditures was assessed according to three food groups: semi-elaborated, industrialized and non-processed food (an emphasis was given to this group). Data on prices to consumer were used to evaluate the relative cost of the products and their influence on household budgets. FB were elaborated using linear programming. RESULTS: From 1990 to 1996, there was a relative increase in household expenditures with industrialized foods and a relative decrease with semi-elaborated foods. The percentage of expenditures with non-processed group revealed an important reduction (35%), but these changes cannot be fully explained by variations in products' prices. Results indicated that household consumption patterns differ from those recommended in the FB and the cost of almost all FB was lower than the actual household expenditures with food. CONCLUSIONS: An inadequate nutritional consumption in São Paulo's households is probable, which carry the risks associated with an insufficient ingestion of vegetables and fruits.